IMPACT OF FLUCTUATIONS IN CRUDE OIL PRICES ON THE JORDANIAN PUBLIC BUDGET FOR THE PERIOD OF 1995-2013 - Bash, Mazen Hassan (European Scientific Journal, ESJ, 2015)
This study aimed to identify the impact of fluctuations in crude oil prices on the Jordanian public budget for the period of 1995 to 2013. To achieve the objective of the study, the researcher used an econometric model of linear regression. This shows the relationship between the study variables using Variance Auto Regressive (VAR) method. To estimate the parameters, ordinary least squares (OLS) method was used. The results of the study showed that there is a statistically significant impact of crude oil prices on the Jordanian public budget deficit. This means that an increase in crude oil prices would result to an increase in Jordanian public budget deficit. The study recommended that crude oil and natural gas sector should grant special status through the development plan implemented. They should bring financial resources and human expertise and modern technology, whether from domestic or foreign sources. Also, they should expand in awarding contracts to foreign companies while maintaining the national rights on economic grounds. The technical and economic problems facing the crude oil sector should be treated. Finally, the latest technology available to increase its contribution to the GDP should be employed.